Globalisation and Education Reforms Paradigms and Ideologies (Globalisation, Comparative Education and Policy Research,, 2018)
This book explores the interrelationship between ideology, the state, and education reforms, placing it in a global context. It examines some of the major education reforms and policy issues in a global culture, particularly in light of recent shifts in quality and standards-driven education, and policy research. The book critiques the neo-liberal ideological imperatives of current education and policy reforms, and illustrates the way the shifts in the relationship between the state and education policy affect current trends in education reforms and schooling globally. With this as its focus, the book's individual chapters highlight hand-picked scholarly research on major discourses in the field of comparative education. A compendium of the very latest thinking on the subject, the book - like the other volumes in the series - offers a state-of-the-art sourcebook for researchers, practitioners and policymakers alike. Not only do the chapters offer a timely overview of current issues affecting comparative education and education policy research in what is now a global educational culture; they also outline future directions that education and policy reforms could take. By doing so, they provide a comprehensive picture of the intersecting and diverse discourses of globalisation and policy-driven reforms in education. Individual chapters critically assess the dominant discourses and debates on education and policy reforms. Using diverse comparative education paradigms from critical theory to historical-comparative research, they address globalisation, ideology and democracy and examine both the reasons for and outcomes of education reforms and policy change. As such, they provide an informed critique of models of quality and standards-driven education reforms that are informed by Western dominant ideologies and social values.